Infestation of Caliothrips phaseoli (Thysanoptera: Thripidae) on bean cultivars grown in the winter, rainy, and dry seasons in Brazil - Boiça Júnior, Arlindo Leal [UNESP]; Costa, Eduardo Neves [UNESP]; Souza, Bruno Henrique Sardinha de [UNESP]; Silva, Anderson Gonçalves da; Chiorato, Alisson Fernando (Oxford University Press, 2015)
The present study aimed to identify common bean (Phaseolus vulgaris L.) cultivars less susceptible to Caliothrips phaseoli (Hood) in different growing seasons, to evaluate whether climatic conditions influence plant resistance to C. phaseoli infestation, and to investigate the preferred plant part for insect feeding. Eighteen common bean cultivars were evaluated in the winter season, and 19 cultivars were assessed in the rainy and dry seasons, under field conditions in the municipality of Jaboticabal, state of São Paulo, Brazil. Infestation of C. phaseoli nymphs in the upper and lower parts of the beans plants was recorded at weekly intervals from 25 days after plant emergence (DAE) to 60 DAE. In the winter season, the cultivars 'IAC Galante,' 'IAC Centauro,' 'IAC Carioca Eté,' and 'IAC Formoso' had significantly lower number of thrips than the cultivar 'IAC Diplomata.' In the rainy season, the cultivars 'IAC Harmonia' and 'IPR Siriri' had the lowest thrips infestation, differing from the cultivars 'BRS Pontal' and 'IAC Una.' The bean cultivars were equally susceptible to C. phaseoli in the dry season. The results suggest that C. phaseoli nymphs prefer to infest leaves of the lower part of bean plants, like most generalist herbivorous insects. In the winter and dry seasons, the highest thrips infestation was observed at 60 DAE, while in the rainy season, it was recorded from 32 to 46 DAE. Overall, C. phaseoli infestation on bean cultivars was not influenced by either temperature, relative humidity, or rainfall.
Keywords: Phaseolus vulgaris l.; Antixenosis; Feeding nonpreference; Host plant resistance; Thrips